Promoting Female Interest in Economics: Limits to Nudges - Todd Pugatch; Elizabeth Schroeder (Institute of Labor Economics (IZA), 2020)
Why is the proportion of women who study Economics so low? This study assesses whether students respond to messages about majoring in Economics, and whether this response varies by student gender. We conducted an experiment among more than 2,000 students enrolled in Economics Principles courses, with interventions proceeding in two phases. In the first phase, randomly assigned students received a message with basic information about the Economics major, or the basic message combined with an emphasis on the rewarding careers or financial returns associated with the major. A control group received no such messages. In the second phase, all students receiving a grade of B- or better received a message after the course ended encouraging them to major in Economics. For a randomly chosen subset of these students, the message also encouraged them to persist in Economics even if their grade was disappointing. The basic message increased the proportion of male students majoring in Economics by 2 percentage points, equivalent to the control mean. We find no significant effects for female students. Extrapolating to the full sample, the basic message would nearly double the male/female ratio among Economics majors. Our results suggest the limits of light-touch interventions to promote diversity in Economics.
Keywords: I21; I23; 330; college major choice; gender gap in economics; higher education; nudges; randomized control trial